2017
DOI: 10.1016/j.str.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The BID Domain of Type IV Secretion Substrates Forms a Conserved Four-Helix Bundle Topped with a Hook

Abstract: In Brief Stanger, de Beer, Dranow et al. describe the novel BID domain fold, revealing a compact four-helix bundle. Their analyses suggest that the conserved shape of BID domains is critical to function as a secretion signal, while low surface conservation facilitates the evolution of secondary functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 23 publications
2
42
0
5
Order By: Relevance
“…Functional annotation of these atypical poly‐Ubs on BepE requires further investigation. Previous study showed amino acid composition of BID domains from different Beps is not well conserved (Stanger et al, ). We also found that lysine residue at site of 365 of Bqu ‐BepE is not identical among BepE orthologues.…”
Section: Discussionmentioning
confidence: 96%
“…Functional annotation of these atypical poly‐Ubs on BepE requires further investigation. Previous study showed amino acid composition of BID domains from different Beps is not well conserved (Stanger et al, ). We also found that lysine residue at site of 365 of Bqu ‐BepE is not identical among BepE orthologues.…”
Section: Discussionmentioning
confidence: 96%
“…On the basis of the solved BID domain structures, the conserved overall fold suggests a crucial role in initial steps of T4SS mediated Bep translocation into host cells. In contrast, the less conserved surface of BID domains seems to have facilitated the evolution of new interaction interfaces with host target proteins, thereby modulating different cellular pathways (Stanger et al, ). We further believe that the high degree of surface variability of BID domains of Bep orthologues might display an adaptive step to fine‐tune host‐restricted interactions.…”
Section: Parallel Evolution Of Complex Bep Repertoiresmentioning
confidence: 99%
“…A comparison of SgEsaA235-829 to previously determined structures in the Protein Data Bank using DALILITE revealed that the overall structure of SgEsaA235-829 does not resemble proteins of known structure (Holm, 2020). The top hit from this search was the BID domain of the type IV secretion system (T4SS) effector protein Bep9 from Bartonella clarridgeiae (Zscore, 8.5; Ca root mean square deviation of 3.5Å over 100 aligned residues), which only shares structural similarity with AD-I of EsaA ( Figure S3) (Stanger et al, 2017). BID domains comprise one part of a bipartite signal sequence found in some T4SS effectors and thus appear unrelated in terms of function.…”
Section: Esaa Forms An Elongated Arrow-shaped Dimermentioning
confidence: 99%